Possibilities for the Flow of Water and Blood through a Graphene Layer in a Geometry Analogous to Human Arterioles: An Observational Study - S. Shankar Narayan; Abdulkafi M. Saeed; Nahid Fatima; Fuad S. Al-Duais; Khalid Abdulkhaliq M. Alharbi; Venkatesh Puneeth; M. R. Gorji; Nidhal Ben Kheder; Shaimaa A. M. Abdelmohsen (Applied Sciences, 2023)
Atherosclerosis and aneurysm are two non-communicable diseases that affect the human arterial network. The arterioles undergo dimensional changes that prominently influence the flow of oxygen and nutrients to distal organs and organ systems. Several studies have emerged discussing the various possibilities for the circumstances surrounding the existence of these pathologies. In the present work, we analyze the flow of blood across the stenosis and the aneurysmic sac in contrast with the flow of water to explore alterations in the flow characteristics caused by introduction of the graphene layer. We investigate the blood flow past the graphene layer with varying porosity. The study is undertaken to replace usage of a stent along a blocked artery by inserting a thin layer of graphene along the flow channel in the post-pathological section of the geometry. To explain the flow, a 2D mathematical model is constructed, and the validity and exclusivity of the model’s solution are examined. When the artery wall is assumed to be inelastic, the computation of the mathematical system is evaluated using a finite element method (FEM) solver. We define a new parameter called critical porosity <semantics>Cεp</semantics> to explore the flow possibilities through the graphene layer. The findings indicate that the flow pattern was adversely affected by the graphene layer that was added to the flow field. The negative impact on the flow could be due to the position of the graphene layer placed. The <semantics>Cεp</semantics> values for the flow of blood across healthy arteriole, stenosed arteriole, and aneurysmic arteriole segments were <semantics>5.7%, 3.5%,</semantics> and <semantics>3.5%</semantics> respectively. The critical porosity values were achieved with precision in terms of linear errors <semantics>8.1×10−12</semantics>, <semantics>7.7×10−12</semantics>, and <semantics>3.9×10−12</semantics>, respectively. The consequences of the present study disclose various possible ways to utilize graphene and its compounds in the medical and clinical arena, with a prior exploration of the chemical properties of the compound. The idea and the methodology applied for the present study are novel as there have been no previous research works available in this direction of the research field.